1958
DOI: 10.1017/s0022029900009249
|View full text |Cite
|
Sign up to set email alerts
|

712. The relation between the chemical composition of milk and the stability of the caseinate complex: I. General introduction, description of samples, methods and chemical composition of samples

Abstract: 1. This paper is Part I of a series dealing with the relation between the chemical composition of milk and the stability of the caseinate complex to ethanol (Part II), rennet (Part III) and heat (Part IV).2. A description is given of the milk samples, which were taken from herd bulk milk, from individual cows in different stages of lactation and also from cows with subclinical mastitis.3. The methods used to measure the stability of the caseinate complex to the three coagulating agents are described, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
2
2

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(73 citation statements)
references
References 24 publications
9
60
2
2
Order By: Relevance
“…On the other hand, Kehoe et al (2007) reported mean concentrations of calcium and phosphate in colostrum which were approximately 4-fold and 5-fold higher than the concentrations found in milk. White and Davies (1958a) reported that the average concentrations of colloidal inorganic calcium and colloidal phosphate were lower in colostrum than in milk. CCP is associated predominantly with casein and is present at higher concentrations in colostrum than in milk (Cerbulis and Farrell 1975).…”
Section: Mineralsmentioning
confidence: 99%
“…On the other hand, Kehoe et al (2007) reported mean concentrations of calcium and phosphate in colostrum which were approximately 4-fold and 5-fold higher than the concentrations found in milk. White and Davies (1958a) reported that the average concentrations of colloidal inorganic calcium and colloidal phosphate were lower in colostrum than in milk. CCP is associated predominantly with casein and is present at higher concentrations in colostrum than in milk (Cerbulis and Farrell 1975).…”
Section: Mineralsmentioning
confidence: 99%
“…The rennet coagulation parameters, the contents of dry matter, ash, Ca, Mg (in milk and skimmed milk ultrafiltrate), and P (in milk, skimmed milk ultrafiltrate and milk after treatment with trichloroacetic acid) were determined as reported in Malacarne et al (2014Malacarne et al ( , 2015. Distribution of Ca, P and Mg fractions were calculated according to White and Davies (1958).…”
Section: Milk Parametersmentioning
confidence: 99%
“…Raw milk generally contains 930 mg/kg of phosphorus (900-1000 mg/kg) where calcium content is often higher (1180 mg/kg) (White and Davies, 1958;Goff and Hill, 1993;Jensen, 1995). Calcium is present in milk in the form of primarily calcium citrate as well as calcium phosphate (in casein) (Jensen, 1995).…”
Section: Implication Of Iron In Bovine Nutritionmentioning
confidence: 99%